The sword and the pen : women, politics, and poetry in sixteenth-century Siena - Eisenbichler, Konrad (Book collections on Project MUSE., 2012)
"In The Sword and the Pen: Women, Politics, and Poetry in Sixteenth-Century Siena, Konrad Eisenbichler analyzes the work of Sienese women poets, in particular, Aurelia Petrucci, Laudomia Forteguerri, and Virginia Salvi, during the first half of the sixteenth century up to the fall of Siena in 1555. Eisenbichler sets forth a complex and original interpretation of the experiences of these three educated noblewomen and their contributions to contemporary culture in Siena by looking at the emergence of a new lyric tradition and the sonnets they exchanged among themselves and with their male contemporaries. Through the analysis of their poems and various book dedications to them, Eisenbichler reveals the intersection of poetry, politics, and sexuality, as well as the gendered dialogue that characterized Siena's literary environment during the late Renaissance. Eisenbichler also examines other little-known women poets and their relationship to the cultural environment of Siena, underlining the exceptional role of the city of Siena as the most important center of women's writing in the first half of the sixteenth century in Italy, and probably in all of Europe. This innovative contribution to the field of late Renaissance and early modern Italian and women's studies rescues from near oblivion a group of literate women who were celebrated by contemporary scholars but who have been largely ignored today, both because of a dearth of biographical information about them and because of a narrow evaluation of their poetry. Eisenbichler's analysis and reproduction of many of their poems in Italian and modern English translation are an invaluable contribution not only to Italian cultural studies but also to women's studies."--Project Muse.